Are working hours complements in production? - Lin Shao; Faisal Sohail; Emircan Yurdagul (Bank of Canada, 2022)
This paper uses Canadian matched employer-employee data to show that working hours are gross complements in production rather than perfect substitutes, as is typically assumed. We exploit within-establishment and individual-level variation in hours and wages to document novel evidence consistent with complementarities in hours worked. Next, we estimate an elasticity of substitution in working hours of 0.69 in the aggregate and between 0.52 and 1.04 at the industry level. We validate our estimates by showing that industries with higher elasticities exhibit greater flexibility in hours. Our findings have important implications for research on labor supply and the efficacy of policies that aim to influence it.
Keywords: E23; J22; J23; J31; 330; Labour markets; Economic models